2021
DOI: 10.3390/antiox10081205
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging Properties of Plant-Derived Natural Biomolecule Para-Coumaric Acid in the Prevention of Oxidative Stress-Induced Diseases

Abstract: Para-coumaric acid (p-CA) is a plant derived secondary metabolite belonging to the phenolic compounds. It is widely distributed in the plant kingdom and found mainly in fruits, vegetables, and cereals. Various in vivo and in vitro studies have revealed its scavenging and antioxidative properties in the reduction of oxidative stress and inflammatory reactions. This evidence-based review focuses on the protective role of p-CA including its therapeutic potential. p-CA and its conjugates possesses various bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…Caffeic and chlorogenic acids did not show significant differences with respect to the CTR, except for the onion fertilized with SBORHP. p -coumaric and gallic acids are antioxidants with diverse physiological functions that are beneficial for human health with ascertained anticancer, anti-inflammatory, and antimicrobial properties [ 25 , 26 , 27 ]. The mechanisms of action of polyphenols are various and complex and depend on their chemical structures.…”
Section: Resultsmentioning
confidence: 99%
“…Caffeic and chlorogenic acids did not show significant differences with respect to the CTR, except for the onion fertilized with SBORHP. p -coumaric and gallic acids are antioxidants with diverse physiological functions that are beneficial for human health with ascertained anticancer, anti-inflammatory, and antimicrobial properties [ 25 , 26 , 27 ]. The mechanisms of action of polyphenols are various and complex and depend on their chemical structures.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, other studies documented the improved oxidative status of male reproductive organs by C. intybus [ 86 , 87 ]. Coumaric [ 92 ], vanillic [ 89 , 90 , 93 , 94 ], and ferulic acids [ 89 , 91 , 95 , 96 ] are phenolic compounds which are widely dispersed in numerous plants and have been extensively investigated for their antioxidant property. In the same manner, C. endivia L. crude extract and the phenolic fraction demonstrated an anti-inflammatory action by decreasing NF-κB, IL-1 β , IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Many current studies reported that para coumaric acid elevates the level or the activity of enzymes that decrease oxidative stress and inflammation [25][26][27]. By inhibiting NF-kB gene which act as transcription factors of pro-inflammatory cytokines, para coumaric acid acts as an anti-inflammatory agent [28]. This could explain the ethnobotanical usage of P. syriaca against many inflammatory diseases.…”
Section: Zhan and Whangmentioning
confidence: 95%